Eksplorasi Produk Aksesoris dari Bahan Limbah Botol Plastik dengan Metode Fabrikasi Sederhana - Niniek Anggriani; Dyan Agustin; Ratna Andriani Nastiti (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Plastic is an element that is widely used in modern human life. There are many benefits of using this plastic but it also brings harm. Plastic waste can pollute the environment, both land and sea and this is very dangerous for human survival. Therefore, efforts need to be made to reduce the amount of plastic waste, one of which is by processing plastic bottle waste into accessory products such as necklaces, bracelets, earrings, mask connectors and so on.Techniques that can be used in the exploration of plastic bottles, especially hard and soft plastic types to become accessories, are simple fabrication methods, including cutting, heating, softening, bending, and forming.. The method used in this service consists of 2 stages, namely the counseling stage by explaining the importance of processing plastic waste and showing examples that have been made and the training stage. With this method, it is hoped that the training participants will get a better picture and be able to be creative. This training activity was carried out in RT 6 RW 2 Lowokwaru Malang with the target participants being young women and housewives. One of the results of this training is a mask connector which is currently very much needed so that it can be sold and can increase skills and family income.